Experimental Validation of a Coexistence Model of IEEE 802.15.4 and IEEE 802.11b/g Networks. (13th July 2010) - Yuan, Wei; Wang, Xiangyu; Linnartz, Jean-Paul M. G.; Niemegeers, Ignas G. M. M.
Abstract : As IEEE 802.15.4 Wireless Sensor Networks (WSNs) and IEEE 802.11b/g Wireless Local Area Networks (WLANs) are often collocated, coexistence issues arise as these networks share the same 2.4 GHz Industrial, Scientific, and Medical (ISM) band. Consequently, their performance may degrade. We have proposed a coexistence model of IEEE 802.15.4 and IEEE 802.11b/g networks, which addresses their coexistence behavior and explains their coexistence performance. As an extension of the previous work, a compact testbed was developed and experiments on the coexistence issues between these networks were conducted. The experiments not only validated the theoretical model but also provided more information and insights about the coexistence issues in the real-life environment.